Cilostazol, a Phosphodiesterase 3 Inhibitor, Moderately Attenuates Behaviors Depending on Sex in the Ts65Dn Mouse Model of Down Syndrome - Tsuji, Masahiro; Ohshima, Makiko; Yamamoto, Yumi; Saito, Satoshi; Hattori, Yorito; Tanaka, Emi; Taguchi, Akihiko; Ihara, Masafumi; Ogawa, Yuko (Frontiers in Aging Neuroscience, 2020)
People with Down syndrome, which is a trisomy of chromosome 21, exhibit intellectual disability from infancy and neuropathology similar to Alzheimer’s disease, such as amyloid plaques, from an early age. Recently, we showed that cilostazol, a selective inhibitor of phosphodiesterase (PDE) 3, promotes the clearance of amyloid β and rescues cognitive deficits in a mouse model of Alzheimer’s disease. The objective of the present study was to examine whether cilostazol improves behaviors in the most widely used animal model of Down syndrome, i.e., Ts65Dn mice. Mice were supplemented with cilostazol from the fetal period until young adulthood. Supplementation significantly ameliorated novel-object recognition in Ts65Dn females and partially ameliorated sensorimotor function as determined by the rotarod test in Ts65Dn females and hyperactive locomotion in Ts65Dn males. Cilostazol supplementation significantly shortened swimming distance in Ts65Dn males in the Morris water maze test, suggesting that the drug improved cognitive function, although it did not shorten swimming duration, which was due to decreased swimming speed. Thus, this study suggests that early supplementation with cilostazol partially rescues behavioral abnormalities seen in Down syndrome and indicates that the effects are sex dependent.